Improvements in Indigenous mortality in the Northern Territory over four decades - John R. Condon; Tony Barnes; Joan Cunningham; Len Smith (Elsevier, 2004)
Abstract Objective:To provide the first report of long‐term mortality trends over recent decades for an Indigenous Australian population. Very little information is available about improvements over time, or lack thereof, in the health status of Indigenous Australians. Methods:Internally consistent time series of deaths and population data were produced for the Indigenous population of the Northern Territory (NT) for 1966-2001. Time trends for Indigenous mortality rates and differentials between NT Indigenous and total Australian rates were examined for 1967-2000. Results:NT Indigenous mortality declined in all age groups and both sexes. The decline was greatest in age group 0-4 (85%). In those aged five years and over, NT Indigenous mortality declined by 30% in females and 19% in males However, these declines did not keep pace with the relative decline for the total Australian population, so that mortality rate ratios (NT Indigenous to total Australian) increased for all age groups except 0-4 years. NT Indigenous mortality declined for communicable, maternal, perinatal and nutritional conditions by 62%, and for injury by 33%, but did not decline for non‐communicable diseases. Conclusions:Indigenous mortality has improved in the NT in recent decades, but the relative gap between Indigenous and other Australians has increased. Implications:Reductions in NT Indigenous mortality reported here may provide some reassurance that improvement in Indigenous health is possible and has occurred, but even greater effort will be required to accelerate the pace of improvement.